Arginine as A Potential Therapy against Ischemic/Reperfusion Injury in Rat Model - Dr. Debopriya Ghosh,; Dr. Sandeep Mukharjee,; Rajasekaran Rajkumar, (International Journal of Pharma and Bio Sciences, 2022)
: Adnexal torsion (Ovarian torsion) is a rare gynaecologic emergency with a prevalence of 2.7%. This denotes the bending of the ovary and fallopian tube around the broad ligament. Early diagnosis and treatment is necessary for the preservation of the affected ovary. Hence, fertility as long-term arterial, venous or lymphatic obstruction of the ovary causes a critical reduction in tissue blood flow and permanent tissue damage. The aim of ischemia treatment is not only to achieve blood flow but also to restore tissue reperfusion. In this study eight weeks old 15 female Adult albino rats (Wister strain) of body weight 130-150 gm gm were used for this experiment . Experimental animals were divided into 3 groups according to their treatment, bull dog clip induced artificial ischemia was induced followed by respective periods of reperfussive time. Treatment with L arginine was performed with dedicated experimental animal group. This study shows that ischemia/reperfusion causes oxidative stress and alteration in ovarian tissue architecture as revealed by increased oedema, vascular congestion clots and tissue degeneration in a rat model of ovarian torsion and the intervention/ therapeutic use of L-arginine could be applied as a therapeutic agents to treat shows that the ischemic/reperfusion mediate alterations in ovarian tissue. The study showed that the decreased oxidative stress parameters and reversal of changes in ovarian architecture after treating with L-Arginine.. Moreover it can be said that the potential effect of L-arginine can be used to reduced I/R injury in rat ovary along with overian torson induced changes in animal models, although more specific and broad study required to use the therapeutic value of L arginine on a clinical setup.